Nationalism and xenophobia in cricket: Identifying distinctions, examining promotion, and proposing solutions - Hasaan, Ali; Fişne, Mücahit; Khalid, Jawaria (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Various forms of racism are present in all types of sports. Xenophobia, in this context, is considered a new type of racism centered around the fear or dislike of foreigners, often intertwined with nationalism. As cricket’s most popular format is matches between countries, this qualitative study aimed to examine whether nationalism in the sport is intentionally or unintentionally spreading xenophobia. A total of 20 participants (6 females and 14 males) from academic and professional cricket backgrounds, comprising sociology scholars, lecturers, PhD students, national-level umpires, professional players, coaches, journalists, and cricket board officials, participated in four focus groups, with five members in each focus group. The findings suggest that nationalism plays a role in partially promoting xenophobia, and within the context of cricket, nationalism may intentionally or unintentionally foster xenophobic attitudes, while also proposing potential policies to mitigate such issues. Overall, the study emphasizes the urgency of tackling xenophobia in cricket through proactive measures promoting inclusivity and combating discriminatory attitudes.